Analisis Keterampian Membaca Cerpen dan Puisi Arab di Madrasah Aliyah Nurul Qadim Probolinggo (International Forum of Researchers and Lecturers, 2025)
As a literary genre with its own appeal, short stories (qishshah qashirah) and poetry (shi'r) offer a unique and beneficial reading experience for students. However, learning to read Arabic literary texts often presents various challenges. This study aims to analyze in depth the reading skills of Arabic literary texts, specifically short stories and poetry, at Madrasah Aliyah. This research employs a qualitative descriptive method, which aims to observe and describe events, phenomena, attitudes, social activities, perceptions, beliefs, and thoughts of individuals or groups. Data collection is conducted through observation, interviews, and documentation. The data analysis technique follows the Miles and Huberman model, which consists of three main stages: data reduction, data presentation, and conclusion drawing. The findings reveal that students' ability to read Arabic literary texts, both short stories and poetry, remains relatively low. Several internal and external factors influence this ability, including limited vocabulary (mufradat), which causes students to struggle in understanding texts, frequently pause, guess word meanings, or even give up entirely. Additionally, weak proficiency in Arabic grammar (nahwu and sharaf) further hinders their comprehension of sentence structures in literary texts. To address these challenges, three strategies can be implemented by educators to enhance students' reading skills: utilizing diverse learning media, selecting engaging and relevant themes, and providing a variety of reading resources.